HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA TERHADAP ABOORSI DI SMK 9 KOTA TANGERANG TAHUN 2020 - Winarni, Lastri Mei (Universitas Muhammadiyah Lamongan, 2021)
Background : Abortion is the process of expulsion from the conception of the fetus before it can live outside the womb. In Indonesia, the incidence of abortion is estimated to reach 2.3 million per year, around 75,000 done by adolescents. The Purpose : of this study is to determine the relationship between the level of knowledge and attitudes of adolescents towards abortion in SMK 9 Kota Tangerang. Research Method : used is descriptive correlation with cross sectional approach.Â collection using a questionnaire with a sample of 132 samples. Sampling using random sampling and test analysis using chi-square. Research Results : showed there was a relationship between the level of knowledge and attitudes of adolescents towards abortion in SMK 9 Tangerang City in 2020 with p value = 0.003â‰¤ 0.05. Conclusion : Â from the results of the study there is a relationship between the level of knowledge and attitudes of adolescents towards abortion